Agriman Agventures. Secrets of the soil - Jeunanne Alkins (W.H.Y. Farm, 2022)
Agriman's agventure kicks off with drought and blazing heat by photosynthesis there are oods moving to a thunderous beat. The weather has been really strange all over the world one minute it's raining, the next it's really hot. What is causing the temperature to change nonstop?